Deepleague’s use of social media as an advertising platform for products and services - Mawere, Delight (Midlands State University, 2019)
In this era of Internet of Things (IoT), new technology innovations are constantly introduced globally however with less developed countries adopting these innovations and ways of doing things at a later stage. This research focuses on one of these innovations which is the use of social media by businesses as an advertising platform for products and services. Various types of businesses in Zimbabwe are embracing this concept of social media advertising but lacking the knowledge on the how to and also the benefits and drawbacks. The phenomenon that is discussed later is on Deepleague which has over the years grown to be one of the biggest E-commerce platforms in Zimbabwe advertising on behalf of other businesses and organizations. This shed more light on the whole process of advertising and the input that is required. Both qualitative and quantitative methods were used in investigating the use. The clients of Deepleague, followers, employees and social media users were interviewed. The study revealed that social media advertising requires skills and knowledge to get tangible benefits, amateur businesses in the advertising on social media still need to gain knowledge of how to interact with consumers as profits are still a challenge. Consumers are the main focus of online advertising as they wield power to determine the success of a business through electronic word of mouth and also interaction with the business. Once a business has achieved and understood the power of online consumers, the benefits are limitless like what Deepleague is enjoying now. The benefits include wide consumer base, low income expenditure since they are online operations, involuntary advertising of business by electronic word of mouth from satisfied consumers to the other among several others. Drawbacks include less tangible profits for the business and government interference affecting the stability of the business.